2010
DOI: 10.1677/joe-10-0036
|View full text |Cite
|
Sign up to set email alerts
|

The TRβ-selective agonist, GC-1, stimulates mitochondrial oxidative processes to a lesser extent than triiodothyronine

Abstract: Specific tissue responses to thyroid hormone are mediated by the hormone binding to two subtypes of nuclear receptors, TRa and TRb. We investigated the relationship between TRb activation and liver oxidative metabolism in hypothyroid rats treated with equimolar doses of triiodothyronine (T 3 ) and GC-1, a TRb agonist. T 3 treatment produces increases in O 2 consumption and H 2 O 2 production higher than those elicited by GC-1. The greater effects of T 3 on oxidative processes are linked to the higher hormonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…However, it is not known whether conditions leading to increased cellular ROS production also involve changes in mitochondrial capacity to remove H2O2. Previously, we found that the capacity of non respiring mitochondria from rat liver is modified by thyroid state, being high in hyperthyroid and low in hypothyroid state (Venditti et al, 2010). This pattern is confirmed by present results, which also show that, in all thyroid states, H2O2 removal significantly increases in the presence of respiratory substrates, in particular pyruvate/malate, even though the highest and the lowest removal rates are yet found in hyperthyroid and in hypothyroid state, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, it is not known whether conditions leading to increased cellular ROS production also involve changes in mitochondrial capacity to remove H2O2. Previously, we found that the capacity of non respiring mitochondria from rat liver is modified by thyroid state, being high in hyperthyroid and low in hypothyroid state (Venditti et al, 2010). This pattern is confirmed by present results, which also show that, in all thyroid states, H2O2 removal significantly increases in the presence of respiratory substrates, in particular pyruvate/malate, even though the highest and the lowest removal rates are yet found in hyperthyroid and in hypothyroid state, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Because GSH contributes to H2O2 mitochondrial metabolism as co-factor of both glutathione peroxidase and peroxiredoxins, we determined its mitochondrial content, which was found to be independent of thyroid state, confirming previous report (Venditti et al, 2010). Interestingly, decreases in GSH mitochondrial content were reported in hyperthyroidism induced by administering T3 to euthyroid rats (Chattopadhai et al, 2010;Venditti et al, 2006), even though we are not able to provide straightforward explanation for this.…”
Section: Tablesupporting
confidence: 75%
“…Findings from different TR knockout mice (e.g. TRα, TRβ, TRα1+m) and the use of isoform-selective agonists indicate specific roles for TH-adrenergic interactions in BAT and white adipose tissue(WAT)45678910. Early studies in thyroidectomized and hypothyroid rats demonstrated the relevance of BAT specific type II iodothyronine deiodinase Dio2 as a local and systemic source of 3,3′,5-triiodothyronine (T 3 ) under cold exposure and for the first time provided evidence for T 3 in the enhancement of the thermogenic response to sympathetic stimulation1112.…”
mentioning
confidence: 99%
“…It has been established in various studies that the changes in thyroid hormone metabolism affect oxidant and antioxidant systems in different ways. Venditti et al (6) reported that T 3 treatment increased oxygen consumption and H 2 O 2 production, while Cano-Europa and colleagues (7) found that hypothyroidism induced by methimazole or thyroidectomy caused cellular damage in rats and that this damage could not be corrected by antioxidant systems. However, it was also established in another study that the effect caused by propylthiouracil (PTU) administration on the oxidant and antioxidant systems changed in a time-dependent manner (8).…”
mentioning
confidence: 99%